Repurposing of gastric cancer drugs against COVID-19. (October 2021) - Sonkar, Charu; Doharey, Pawan Kumar; Rathore, Anuranjan Singh; Singh, Vishal; Kashyap, Dharmendra; Sahoo, Amaresh Kumar; Mittal, Nitish; Sharma, Bechan; Jha, Hem Chandra
Abstract: Corona Virus Disease 2019 (COVID-19) caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has become a global pandemic. Additionally, the SARS-CoV-2 infection in the patients of Gastric Cancer (GC; the third leading cause of death in the world) pose a great challenge for the health management of the patients. Since there have been uncertainties to develop a new drug against COVID-19, there is an urgent need for repurposing drugs that can target key proteins of both SARS-CoV-2 and GC. The SARS-CoV-2-RdRp protein contains the NiRAN domain, which is known to have kinase-like folds. A docking study of the FDA approved drugs against GC was performed using AutoDock 4.2 and Glide Schrodinger suite 2019 against SARS-CoV-2-RdRp protein. MMGBSA and MD simulation studies were performed to investigate the binding and stability of the inhibitors with the target protein. In this study, we have found 12 kinase inhibitors with high binding energies namely Baricitinib, Brepocitinib, Decernotinib, Fasudil, Filgotinib, GSK2606414, Peficitinib, Ruxolitinib, Tofacitinib, Upadacitinib, Pamapimod and Ibrutinib. These FDA approved drugs against GC can play a key role in the treatment of COVID-19 patients along with GC as comorbidity. We also hypothesize that JAK, ITK, Rho-associated kinases, FGFR2, FYN, PERK, TYK2, p38-MAPK and SYK kinases can be considered as key therapeutic targets in COVID-19 treatment. Taken altogether, we have proposed the SARS-CoV-2-RdRp as a potential therapeutic target through in-silico studies. However, further in-vitro and in-vivo studies are required for the validation of the proposed targets and drugs for the treatment of COVID-19 patients already suffering from GC. Highlights: Gastric Cancer patients are a vulnerable group for COVID-19 infection. SARS-CoV-2-RNA dependent RNA polymerase is pivotal protein for viral replication. SARS-CoV-2-RdRP-NiRAN (nucleotidyltransferase) domain has kinase like properties. Kinase inhibitors like brepocitinib, decernocitinib, filgotinib and ibrutinib can be used for COVID-19 treatment.